Graphical interface-based automated music composition use among elementary school students. (March 2014) - Huang, Chih-Fang; Yeh, Yun-Sheng
To facilitate music composition among children and students, this study examined the properties of automated music composition, attempting to leverage this advanced technique to provide children with an easy-to-learn and easy-to-accomplish method of composing music. Consequently, a graphical interface-based automated music composition (GBAMC) software program was developed, yielding enhanced usability, sequenced design, graphical technology, auditory learning, and intelligence. Learning satisfaction and attitude were surveyed among sixth-grade elementary school students (age = 12 years), indicating that students typically exhibited high levels of learning satisfaction and a positive learning attitude; learning satisfaction and attitude were also positively and significantly correlated in each dimension. Finally, recommendations were proposed for future studies to help users enjoy music composition without requiring an extensive background in musical theory.